Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 90 Pekanbaru: (The Effect of Problem-Based Learning Model on 4th Grade Mathematics Learning Outcomes) - Rifda Rila Alvionita; Lilis Marina Angraini (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: This study examines the impact of the Problem-Based Learning (PBL) model on the mathematics learning outcomes of fourth-grade students at SDN 90 Pekanbaru. Methodology: The research utilized an experimental design and purposive sampling, encompassing the entire fourth-grade student population for the academic year 2022/2023, totaling 124 students. The IVD class was the experimental group, while the IVC class served as the control group. The data collection methodology utilized a testing technique, and subsequent analysis incorporated both descriptive and inferential statistical methods. Findings: Upon calculation of the t-test, a significant t-value of 5.665 was obtained with a significance level of α = 0.05. This result highlights the effectiveness of the PBL model in enhancing the mathematics learning outcomes of fourth-grade students at SDN 90 Pekanbaru. Significance: The findings suggest that incorporating PBL into mathematics education can positively influence the academic achievements of elementary students, extending beyond the classroom. This research provides valuable insights into innovative pedagogical approaches as education continues to evolve.